Hungarian Monitoring, 19 March 1989 . [Magyar rádiófigyelő], 1989. március 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Italian CP congress continues - Demonstration in support of Boris Yeltsin in Moscow - Western press reports of Romania selling Western food aid for hard currency - Bucharest's international isolation worsens - Will there be a bicameral parliament in Poland? - Islamic conference Domestic Affairs: - Alliance of Free Democrats (SZDSZ) general assembly - Kálmán Kulcsár speaks to British TV station Channel 4 on the multi-party system - Cardinal Primate Paskai pays private visit to Pope John Paul II - György Konrád on the quiet revolution - Interview in Vienna with Béla Király, former leader of revolutionary forces committee, commander-in-chief of national guard Economy: - Agriculture at a crossroads Külpolitika: - Folytatódik az olasz KP kongresszusa - Moszkvában tüntettek Boris Jelcin mellett - Nyugati lapjelentés szerint Románia valutáért eladja a nyugati élelmiszer segélyeket - Szélesedik Bukarest nemzetközi elszigetelődése - Lesz-e kétkamarás parlament Lengyelországban? - Iszlám konferencia Belpolitika: - SZDSZ közgyűlés - Kulcsár Kálmán a többpártrendszerről nyilatkozik a brit TV4-nek - Paskai bíboros-prímás magánlátogatása II. János Pál pápánál - Konrád György a csendes forradalomról - Bécsi interjú Király Bélával, az egykori forradalmi karhatalmi bizottság vezetőjével, a nemzetőrség országos parancsnokával Gazdaság: - Válaszúton a mezőgazdaság